State Ownership: A Literature Review - Cahya Purnama Asri (Profesional Muda Cendekia Publishing, 2022)
State ownership enterprises (SOEs) are always been considered to be less efficient, both in productivity and innovation. SOEs are more likely to do nothing and to maintain the existing advantages due to agency problems The objective of this research is to provide a review of the literature which is exhaustive, especially about state ownership. We presented a literature study and included 14 articles as a result. The result shows some variables that are affected by state ownership and a variable that affects state ownership. Further research is suggested to further explore the variables that affect state ownership.